Assessment of the bending capacity of welded hollow spherical joints with pit corrosion. (October 2018) - Zhao, Zhongwei; Liu, Haiqing; Liang, Bing
Abstract: Welded hollow spherical joints (WHSJs) are widely used in space lattice structures. Corrosion is inevitable for WHSJs during service, and this phenomenon will significantly reduce loading capacity and seriously threaten the structural safety. Pit corrosion is a typical corrosion type for steel structures. In this study, nonlinear numerical analyses were conducted to investigate the influence of several parameters on the bending capacity of a WHSJ. A numerical model of the WHSJ with random pit corrosion was proposed to investigate the mechanical behavior of the corroded WHSJ. Results indicated that the moment capacity of the WHSJ with random corrosion pits was normally distributed. A probabilistic distribution model of the corroded WHSJ was proposed. The failure probability could be deduced based on the formulae of the upper and lower bounds of the moment capacity. Highlights: Influence of pit corrosion on bending capacity of corroded welded hollow spherical joints was investigated. Numerical model of WHSJ with random pit corrosion was proposed. The moment capacity of WHSJ with random pit corrosion is normally distributed. The probabilistic distribution model of corroded WHSJ with random pit corrosion was proposed.